Analisis Aktivitas Belajar Siswa Berprestasi dalam Pembelajaran Matematika - Saharia; Suradi Tahmir; Nurwati Djam’an (Issues in Mathematics Education (IMED), 2017)
The type of research is a qualitative research using descriptive approach. This subject research is 3 students who come from one of private schools in Makassar with highest score of mathematical and had ever followed mathematics olympiad. To know learning activities of student with high achievement SMP Islam Athirah Makassar conducted several techniques of data collection is observation, interview, and field notes. The data analysis techniques used are data exposure, reduction, presentation, conclusions and verification. Based on the result of research and discussion obtained learning activities of students with high achievement is pay attention and listen explanation well, writing / recording material written by her teacher, active on learning process, tutoring in class, always expressed opinion, became tutor in class, immediately doing the tasks given by her teacher, always doing the exercises of the Olympics, always taking the time to study mathematics in school and outside school, studying mathematics in various references, following the tutorial of studying olympiad at school, follow the guidance of study or courses outside school, follow the quarantine at school before the Olympic race.